Novel synthesis of steroidal oximes and lactams and their biological evaluation as antiproliferative agents - Martínez Pascual, Roxana; Meza-Reyes, Socorro; Vega-Baez, José Luis; Merino-Montiel, Penélope; Padrón, José M.; Mendoza, Ángel; Montiel-Smith, Sara (Steroids, 2017)
A novel three-step methodology to obtain 6a-aza-B-homo steroidal lactams has been developed starting from the easily available cholesterol and pregnenolone. In addition, a new procedure for the synthesis of a 6a-aza-B-homo steroidal lactam analog of vespertilin, starting from diosgenin has been established. In both synthetic pathways, the key intermediate is a hydroxyimino derivative obtained in a one- or two-step sequence from the starting materials. These methods avoid the use of hazardous oxidant agents in the process. The new steroidal oximes and lactams were examined for their antiproliferative activities against several tumor cell lines. The 6,23-dihydroxyimino derivative exhibited the highest activity with GI50 values of 11–22 µM.
Keywords: Lactamas esteroidales; Síntesis orgánica